(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Through the comparative analysis of China's national and international standard systems on chemical protective clothing (CPC), this paper summarizes the differences in classification and minimum performance requirements between several standard systems. The study provides the most basic performance assessment factors for all types of CPC. It can also be observed that the standard systems of European Standards (EN) and the International Organization for Standardization (ISO) have similar classifications and performance requirements for CPC, while China's standard systems (GB) mainly give detailed requirements for emergency team CPC as a supplement for previous international standards.